Burnout and Contributing Factors to Burnout Among Indonesian Healthcare Workers Before and During COVID-19 Pandemic - Simbolon, Monalisa; Basabih, Masyitoh (Jurnal Psikiatri Surabaya, 2023)
Introductions: The prevalence of burnout among health workers in Indonesia varies. During the Coronavirus Disease 2019 (COVID-19) pandemic, there was an increase in burnout among health workers. Many factors can affect the prevalence of burnout in health workers. Objectives: to provide an overview of the prevalence and factors that influence burnout among healthcare workers in Indonesia. Methods: The writing of this article uses the literature search method. Literature searches used the Pubmed and Google Scholar search engines, using literature within a time limit of 3 years before and three years during the COVID-19 pandemic. Results: It is known that the prevalence of burnout before the COVID-19 pandemic reached 19.8%–62.85%, and during the COVID-19 pandemic reached 5.2%–82%. For factors that affect burnout before and during the COVID-19 pandemic, there is not much difference between factors such as age, gender, marital status, type of work, workload, stress level, length of service, number of hours worked per week, and level of education. In several studies before the COVID-19 pandemic, additional factors such as religiosity, work environment, and organizational structure leadership were found. In contrast, during the COVID-19 pandemic, there were other risk factors, namely the risk of transmission of COVID-19, educational background, and access to psychological services. Conclusions: By knowing the factors related to burnout, it is hoped that it can be used as a step to form an effective and efficient management system to overcome burnout